The Pragmatist Tradition: Lessons for Legal Theorists - Susan Haack (Washington University Law Review, 2018)
As you probably noticed, my title is ambiguous—deliberately so, because my purpose here is twofold: to teach legal theorists something of the pragmatist tradition in philosophy, its history, its character, and its content; and to suggest some of the ways in which the intellectual resources of that tradition can enhance our understanding of the law. And as you probably also noticed, my opening quotation is two-sided—again, deliberately so, because I hope to achieve two things: to convey some sense of the rich potential of classical pragmatism to illuminate issues in legal theory; and to reveal something of the poverty and crudeness of the caricatures of pragmatism that, sadly, seem to be as common in legal circles as they are in the philosophical mainstream. Some of you may suspect that I’ve already set out on the wrong foot. Isn’t pragmatism, after all, inherently anti-theoretical—and doesn’t that mean that both my title, and my project, must be misconceived? Not at all. Perhaps the misconception results from a confusion of the ordinary language meaning of “pragmatism” (“a practical approach to problems,” “dealing with matters with respect to their practical consequences,” concern for political or practical expediency rather than principle) with its specialized philosophical meaning; perhaps it results from a confusion of the regular use of “theory” with its recent specialized use by legal scholars to refer to systematic prescriptions about how the law should be interpreted. But whatever the reason, the idea that pragmatism (in the philosophical sense) is hostile to theory (in the regular sense of “explanatory account”) is way off the mark. The philosophers of the classical pragmatist tradition were in no way anti-theoretical; neither was legal pragmatist Oliver Wendell Holmes—who believed, on the contrary, that “we have too little theory in the law rather than too much”; and neither, of course, am I. However, the usual fare of analytic legal theory—all too often preoccupied with its own internecine disputes, and operating at such a dizzyingly high level of generality and abstraction that it fails to engage with any actual legal system in its particularity—is, to my way of thinking, too thin, too bloodless, and too idealized; and the usual fare of recent legal Theory-with-a-capital-T—focused in large part on the idea that law should be viewed through the lens of race, gender, etc.—too narrow, too parochial, and too politicized. Pragmatist legal theory offers us something better than either. Unlike analytic philosophy, pragmatism invites us to focus, not exclusively on our language or our concepts, but on the world; and so, in the legal sphere, not exclusively on the concept of law but on the phenomenon of law—law as embodied in real legal systems. And, unlike recent capital-T legal Theory, pragmatist legal theory aspires not to prescribe how the law should be interpreted, but to suggest how to understand the origin, the evolution, and the functions of the myriad legal systems of the world. Of course, it’s quite impossible, in one short paper, to give anything like a full account either of the history of the pragmatist tradition in philosophy, or of the insights the ideas of that tradition might offer to legal theory—let alone to do both. Here, the relatively modest goal is, first, to sketch the origins and evolution of pragmatism in enough detail to convey some sense both of the predilections and attitudes that the old pragmatists shared, and of the enormous variety of their ideas (Part I); then, to explore Oliver Wendell Holmes’s and other legal thinkers’ role in this story (Part II); next, to look briefly at how some influential forms of neo- or, more exactly, pseudo-pragmatism have distorted our understanding, and weakened our appreciation, of this tradition (Part III); and finally to articulate some of the lessons those old pragmatists might teach us about the scope and the growth of law (Part IV).
Keywords: Pragmatism; Pseudo-pragmatism; Neo-pragmatism; Legal theory; Legal pragmatism; Legal philosophy